Correlation among quality parameters of parthenocarpic cucumber genotypes during storage - Tripathi, Vishal; Singh, Vijay K; Kumari, Amrita; Bhardwaj, Ajay; Singh, Paramveer (Journal of Postharvest Technology, 2021)
An experiment was conducted on 37 parthenocarpic cucumber genotypes at Bihar Agricultural University, Sabour in 2019 which was laid out in completely randomized design with four replications and Pearson‘s correlation matrix was analysed for physiological loss in weight (PLW), firmness, titratable acidity (TA), total soluble solids (TSS), chlorophyll and carotenoid content on 0, 4 and 7 days of storage at 24 ± 2 ºC and 60- 80 % relative humidity (ambient condition). The study revealed that quality parameters TA and TSS showed a small correlation while, PLW exhibited moderate correlation in inverse direction with fruit firmness. Moreover, a positive correlation was also exhibited between TSS and PLW in cucumber during storage under ambient conditions.